2010
DOI: 10.1103/physrevlett.105.237201
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Control of Spin Precession Motion with Impulsive Magnetic Fields of Half-Cycle Terahertz Radiation

Abstract: Coherent control of the precession motion of magnetizations in a single crystal YFeO3 with double half-cycle pulse terahertz waves was demonstrated. Quasiferromagnetic (0.299 THz) and quasiantiferromagnetic (0.527 THz) precession modes were selectively excited by choosing an appropriate interval of two pulses and were observed as free induction decay (FID) signals from the spin system. By observing the circularly polarized FID signals due to ferromagnetic resonance, we also succeeded in confirming directly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 18 publications
7
126
0
2
Order By: Relevance
“…By analyzing absorption peaks in the normalized Fourier spectra of the pulses transmitted through the sample, one can obtain information about the spectrum of THz excitations in the sample. The details of the time-domain THz spectroscopy setup can be found elsewhere [22][23][24][25][26][27]. We analyze the THz transmission through the sample in terms of the normalized loss function σ (ω), defined as…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing absorption peaks in the normalized Fourier spectra of the pulses transmitted through the sample, one can obtain information about the spectrum of THz excitations in the sample. The details of the time-domain THz spectroscopy setup can be found elsewhere [22][23][24][25][26][27]. We analyze the THz transmission through the sample in terms of the normalized loss function σ (ω), defined as…”
Section: Appendixmentioning
confidence: 99%
“…It has been demonstrated that broadband pulses of THz radiation can serve as a probe of spin resonances in YFeO 3 [22][23][24], ErFeO 3 [25], NdFeO 3 [26], and Tb 3 Ga 5 O 12 [27]. A promising approach to control magnetic order with the help of intense-enough THz pulses has been suggested for NiO [28].…”
Section: Introductionmentioning
confidence: 99%
“…25 Similarly, an all-THz experiment involving a pair of much weaker THz pulses was used for coherent control of the spin precession in yttrium orthoferrite (YFeO 3 ). 27 In this paper, we show the coherent control of the quasi-FM spin resonance at the frequency of 0.3 THz in the canted AFM crystal YFeO 3 using only a single incident THz pulse. The amplitude and the phase of the THz spin waves can be controlled coherently by choosing the polarization of the incident THz pulse with respect to the symmetry axes of the anisotropic crystal.…”
Section: Thz Excitation and Coherent Control Of Spin Resonances Vmentioning
confidence: 99%
“…16,17 Recently, the ultrafast THz spectroscopy also proved to be an effective experimental method of detection and manipulation of magnetization in materials utilizing the magnetic field component of the THz transient through magnetic dipole transitions. [18][19][20][21][22] In this fashion, the ultrafast magnetization dynamics in ferromagnetic (FM) 23 and antiferromagnetic (AFM) materials [24][25][26][27] have been investigated.…”
Section: Thz Excitation and Coherent Control Of Spin Resonances Vmentioning
confidence: 99%
See 1 more Smart Citation